1995
DOI: 10.1159/000213732
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Age Pigment Accumulation in the Brain Cells of Young Male Rats Through Iron-Injection Into the Cerebrospinal Fluid

Abstract: The OH. free radical formation can be increased in the brain by intralumbar iron injections into the cerebrospinal fluid (CSF) through the Fenton reaction. Ferrous ammonium sulphate was injected to male CFY rats of 3 months of age. The animals survived a single dose of 4 umoles, and this treatment was repeated daily for 3 or 6 days. The total iron contents of the large brain and the cerebellum were measured by atomic absorption spectroscopy; 3 days of iron administration resulted in significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Mitochondria are the primary organelle for oxygen radical production via the respiratory chain. Zs-Nagy et al [32] also reported that the cerebellum was a region where Fe 2+ accumulated. By analysis of the Mn SOD activity of the six brain regions at different ages, we found that the activity was lower in the frontal and occipital lobes of 1-month-old rats ( fig.…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondria are the primary organelle for oxygen radical production via the respiratory chain. Zs-Nagy et al [32] also reported that the cerebellum was a region where Fe 2+ accumulated. By analysis of the Mn SOD activity of the six brain regions at different ages, we found that the activity was lower in the frontal and occipital lobes of 1-month-old rats ( fig.…”
Section: Discussionmentioning
confidence: 95%
“…54 Earlier studies demonstrated that enhanced amounts of lysosomal redoxactive iron accelerated the lipofuscin accumulation in cultured human glial cells 139 and neonatal rat cardiac myocytes, 140 while in rat brain neurons the lipofuscin content was increased by intralumbar injections of iron. 141 Further supporting the involvement of iron and oxidation in lipofuscin accumulation, the iron chelator desferrioxamine and various antioxidants (e.g. vitamin E, selenium, glutathione, etc.)…”
Section: Characteristics Of Age-related Damagementioning
confidence: 95%
“…These include the ubiquitous lipofuscin (Serot et al, 2000;Wen et al, 1999), or age-pigment, that accumulates in all long-lived cell types and is considered to be a product of lipid peroxidation by oxygen free radicals (Zs-Nagy et al, 1995). From middle age, there is also a marked increase in protein inclusions, notably Biondi ring tangles in the epithelium (Eriksson and Westermark, 1986;Wen et al, 1999).…”
Section: Age-related Alterations To the Mammalian Choroid Plexus Morpmentioning
confidence: 99%